Morphology of Lichen Fungi in Amban Regency, Manokwari, West Papua - Nebore, Idola Dian Yoku; Lefaan, Paskalina Th.; Massora, Maria; Nunaki, Jan H.; Dewi, Resmila; Fatem, Sepus Marten (Jurnal Biologi Tropis, 2025)
Lichens are symbiotic association between fungi (mycobionts) and photosynthetic partners (phycobiont) that play essential ecological roles as bioindicators, pioneers in succession, and contributors to nutrient cycling. Despite their importance, the diversity and morphology of lichens in West Papua remain poorly documented. This study aimed to assess the morphology diversity of lichen taxa in Amban Regency, Manokwari, West Papua. The method used was explorative surveys with purposive sampling in Amban Regency (site I, II, and III) based on low, moderate, and high air quality. Lichen identification was based on morphological characteristic. The results showed that there were 27 species lichens belong to 12 genera and 8 families Chrysothrichaceae, Coenogoniaceae, Collemataceae, Graphidaceae, Megalosporaceae, Parmeliaceae, Physciaceae, and Strigulacea. The dominant species were from the families of Graphidaceae. Crustose lichens dominated (74%), foliose lichens (18%), with filamentous and leprose (4% each), while fruticose types were absent. Crustose lichens exhibited strong substrate adhesion and tolerance to variable microclimatic conditions with temperatures between 26,1-29,3°C, whereas foliose and filamentous forms were confined to more stable, and humid habitats between 72,0-85,4%. Continued surveys are recommended to monitor potential shifts in community composition under climate change and habitat disturbance.